Sustainable Asphalt Mixtures Reinforced with Basic Oxygen Furnace Steel Slag: Multi-Scale Analysis of Enhanced Interfacial Bonding - Bin Lei; Linjie Yu; Jiawu Chen; Yuan Meng; Dong Lu; Ning Li; Fulin Qu (Case Studies in Construction Materials)
Utilizing Basic Oxygen Furnace Slag (BOFS) to enhance the pavement performance of the asphalt mixtures is a promising strengthening strategy. However, the academic literature still needs to explore the interfacial dynamics and underlying mechanisms. This study introduces fractal dimension analysis to quantify the Interfacial Transition Zone (ITZ) characteristics in asphalt mixtures incorporating BOFS. A multi-scale analysis of the ITZ performance was conducted on three types of asphalt mixtures: Full Proportion Steel Slag Asphalt Mixture (100SSA-AM), Full Proportion Basalt Asphalt Mixture (100NCA-AM), and Asphalt Mixture of Coarse Aggregate Steel Slag and Fine Aggregate Basalt (Hybrid-AM). The results indicate that compared to the conventional 100NCA-AM, the splitting tensile strength and cracking index of 100SSA-AM and Hybrid-AM increased by 22.2 %, 28.1 %, and 13.5 %, 7.1 %, respectively. The total porosity of 100SSA-AM and Hybrid-AM increased by 58.4 % and 47.2 %, respectively, while the fractal dimension of the pores slightly decreased. In addition, compared to 100NCA-AM and 100SSA-AM, the ITZ fractal dimension of Hybrid-AM increased by 7.03 % and 3.79 %, respectively. In terms of interfacial nanomechanics, the ITZ indentation modulus of 100SSA-AM increased by 14.6 %, and the ITZ width increased by 43.5 % compared to 100NCA-AM, whereas for Hybrid-AM, the ITZ indentation modulus increased by 43.5 % and the ITZ width decreased by 26.1 %. Moreover, the study further revealed that the width and nanomechanical properties of the ITZ are closely associated with the surface roughness and chemical affinity of the aggregates, which holds significant implications for the design and application of sustainable pavement materials.